In Vitro Antagonism Of Rhizoctonia Solani by Trichoderma Species - Tapwal, Ashwani; Kumari, Shruti; Harsh, N. S. K. (Indian Forester, 2014)
In present study, the efficacy of Trichoderma harzianum and four isolates of Trichoderma longibrachiatum were evaluated in laboratory conditions for the management of Rhizoctonia solani. The results revealed that the selected Trichoderma species has restricted 10.6-48.8% mycelial growth in dual culture and 2.0-20.0% by volatile metabolites.